2016
DOI: 10.1016/j.virol.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The genomic sequence of lymphocryptovirus from cynomolgus macaque

Abstract: Lymphocryptoviruses such as Epstein-Barr virus (EBV) cause persistent infections in human and non-human primates, and suppression of the immune system can increase the risk of lymphocryptovirus (LCV)-associated tumor development in both human and non-human primates. To enable LCV infection as a non-clinical model to study effects of therapeutics on EBV immunity, we determined the genomic DNA sequence of the LCV from cynomolgus macaque, a species commonly used for non-clinical testing. Comparison to rhesus maca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In order to examine the incidence of LCV reactivation among HSCT recipient cynomolgus macaques in this study, we developed a quantitative PCR assay to detect cynomolgus lymphocryptovirus (CyLCV) by adapting a previously reported quantitative PCR assay for the rhesus lymphocryptovirus EBER‐1 coding region . We detected cynomolgus LCV (CyLCV) plasma viremia in 67% (6/9) of studied HSCT recipient cynomolgus macaques post‐HSCT (Figure B, Table S1), which is in line with EBV reactivation rates reported in T‐cell‐depleted HSCT patients …”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the incidence of LCV reactivation among HSCT recipient cynomolgus macaques in this study, we developed a quantitative PCR assay to detect cynomolgus lymphocryptovirus (CyLCV) by adapting a previously reported quantitative PCR assay for the rhesus lymphocryptovirus EBER‐1 coding region . We detected cynomolgus LCV (CyLCV) plasma viremia in 67% (6/9) of studied HSCT recipient cynomolgus macaques post‐HSCT (Figure B, Table S1), which is in line with EBV reactivation rates reported in T‐cell‐depleted HSCT patients …”
Section: Resultsmentioning
confidence: 99%
“…This improvement also decreases the price of sequencing, although the cost of library preparation is increased. There are alternative approaches for the enrichment of viral reads, including pulsed-field gel electrophoresis (PFGE) 105 , which separates large viral genomes from smaller fragments of host DNA. Enrichment techniques that use degenerate RNA or DNA probes to capture hundreds of viral species have also been developed; for example, virome capture sequencing (VirCapSeq) 106 .…”
Section: Box 2 | Whole-genome Sequencing Of Zika Virusmentioning
confidence: 99%
“…Schmidtko and others reported that among 160 consecutive renal transplant recipients of cynomolgus monkeys (Macaca fascicularis), 5.6% developed lymphoproliferative lesions similar to human PTLD in incidence, morphology, and immunophenotype [37]. Lymphoblastoid cells in these lesions were shown to be infected with LCV inherent to cynomolgus macaques (cyLCV; Macacine gammaherpesvirus 10) [39,40].…”
Section: Lpd/lymphoma Induced By Lcvs Inherent To Nhps In Immunocomprmentioning
confidence: 99%